IMPACT OF SOCIAL CAPITAL ON BUSINESS RESULTS OF ENTERPRISES - TEXTILE AND GARMENT INDUSTRY IN THE - Tran, Ai Huu; Tran, Dung Anh (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Social capital has a long history of development in economically developed countries. Business results of enterprises are significantly increased when applying social capital. Qualitative research is used in the following order: (1) Find new factors and relationships between social capital and business results, (2) Calibrate the scale of each factor of the model to suit the textile industry. Then, combine it with quantitative exploratory research with the tool Exploratory Factor Analysis (EFA), Test the reliability coefficient, Confirmatory Factor Analysis (CFA), Test the model and research hypothesis. research (CB-SEM) and Bootstrap testing in the theoretical model, there are 6 research factors: (1) Leadership social capital, (2) Internal social capital, (3) External social capital, (4) Acquisition of knowledge, (5) Enterprise product innovation and (6) Business results